The Complete Chloroplast Genome Sequences of Five Epimedium Species: Lights into Phylogenetic and Taxonomic Analyses - Zhang, Yanjun; Du, Liuwen; Liu, Ao; Chen, Jianjun; Wu, Li; Hu, Weiming; Zhang, Wei; Kim, Kyunghee; Lee, Sang-Choon; Yang, Tae-Jin; Wang, Ying (Frontiers in Plant Science, 2016)
Epimedium L. is a phylogenetically and economically important genus in the family Berberidaceae. We here sequenced the complete chloroplast (cp) genomes of four Epimedium species using Illumina sequencing technology via a combination of de novo and reference-guided assembly, which was also the first comprehensive cp genome analysis on Epimedium combining the cp genome sequence of E. koreanum previously reported. The five Epimedium cp genomes exhibited typical quadripartite and circular structure that was rather conserved in genomic structure and the synteny of gene order. However, these cp genomes presented obvious variations at the boundaries of the four regions because of the expansion and contraction of the inverted repeat (IR) region and the single-copy (SC) boundary regions. The trnQ-UUG duplication occurred in the five Epimedium cp genomes, which was not found in the other basal eudicotyledons. The rapidly evolving cp genome regions were detected among the five cp genomes, as well as the difference of simple sequence repeats (SSR) and repeat sequence were identified. Phylogenetic relationships among the five Epimedium species based on their cp genomes showed accordance with the updated system of the genus on the whole, but reminded that the evolutionary relationships and the divisions of the genus need further investigation applying more evidences. The availability of these cp genomes provided valuable genetic information for accurately identifying species, taxonomy and phylogenetic resolution and evolution of Epimedium, and assist in exploration and utilization of Epimedium plants.